2014
DOI: 10.1111/bjso.12091
|View full text |Cite
|
Sign up to set email alerts
|

Feeling like a group after a natural disaster: Common ingroup identity and relations with outgroup victims among majority and minority young children

Abstract: We conducted a field study to test whether the common ingroup identity model (Gaertner & Dovidio, 2000, reducing intergroup bias: The common ingroup identity model. Philadelphia, PA: Psychology Press) could be a useful tool to improve intergroup relations in the aftermath of a natural disaster. Participants were majority (Italian) and minority (immigrant) elementary school children (N = 517) living in the area struck by powerful earthquakes in May 2012. Results revealed that, among majority children, the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 89 publications
7
68
0
Order By: Relevance
“…The distinction between Italians and immigrants was made based on indications by the schools and by taking into account the family background of students (i.e., both Italian parents for Italian participants; both foreign parents for immigrant participants). This distinction is commonly used in research considering data collected in Italy, especially concerning data from both majority and minority groups (e.g., Vezzali, Cadamuro, Versari, Giovannini, & Trifiletti, 2015; Visintin, Voci, Pagotto, & Hewstone, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The distinction between Italians and immigrants was made based on indications by the schools and by taking into account the family background of students (i.e., both Italian parents for Italian participants; both foreign parents for immigrant participants). This distinction is commonly used in research considering data collected in Italy, especially concerning data from both majority and minority groups (e.g., Vezzali, Cadamuro, Versari, Giovannini, & Trifiletti, 2015; Visintin, Voci, Pagotto, & Hewstone, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Also, while trying to reduce post‐traumatic stress symptoms in the population, practitioners can “make use” of them to enhance awareness that other survivors are affected by the very same symptoms and that the community as a whole is involved in the disaster. Increased one‐group perceptions should in turn be one predictor of reduced intergroup conflict among both majority and minority members (Gaertner & Dovidio, ), also in the aftermath of a natural disaster (Andrighetto et al, ) and when children are involved (Vezzali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals were also more likely to report beter social well-being and were less likely to withdraw socially in the aftermath of disasters. Along the same lines of research as Kaniasty and Norris [15], Vezzali and colleagues [16] studied children who were afected by two major earthquakes. They found that symptoms of postraumatic stress were positively associated with a tendency to help other survivors and to build social bonds, possibly as a coping mechanism.…”
Section: Sufering and Prosocial Growthmentioning
confidence: 99%
“…That is, those who sufered may often choose to provide social or informational support instead of tangible material support. Moreover, the driving force behind such preferences for prosociality may not be driven by empathy but instead by other mechanisms such as self-other similarity or communal orientation [16,20].…”
Section: A General Model Of Sufering and Prosocial Growth Via Empathymentioning
confidence: 99%